Biomass production and essential oil of Lippia origanoides (Verbenaceae) due to chemical fertilizer levels and organic. - Sugai, Maria Aparecida Alves; Moreira, Erica Rodrigues [UNESP]; Barros, Hélio Bandeira; Siebeneichler, Susana Cristine; Salimena, Fátima Regina Gonçalves; Erasmo, Eduardo Andrea Lemus; Leal, Tarcísio Castro Alves de Barros (My University, 2020)
The aim of this study was to evaluate the growth of plants of Lippia origanoides using organic fertilizer and chemical for the production of biomass and essential oil. The experimental design was completely randomized, with 8 treatments and 10 repetitions: T1: 40 kg N/ha; T2: 60 kg N/ha; T3: 120 N kg/ha; T4: 60 kg N, P2 O5 and K2 O/ha; T5: 3,1 tons/ha of cattle manure (EB); T6: 4,6 tons/ha of cattle manure (EB); T7: 9,2 tons/ha of cattle manure (EB); T8: Control-without fertilizer. The fertilizer consisted of urea, superphosphate and potassium chloride. We evaluated the absolute growth and stem diameter every 30 days and leaf area, dry weight of leaf, dry mass of the stem, root dry mass, mass dry total, root length, essential oil content, macronutrients and foliar micronutrients to 150 days. The fertilization with manure and NPK fertilization favored growth, stem diameter, leaf area and total dry mass. The fertilization with 4.6 t/ha of manure showed the highest absolute growth of L. origanoides to 150 days of cultivation. Increased production of essential oil and P content and accumulation of Zn in the leaves was obtained at a dose of 9.2 t/ha of manure. The NPK fertilization favored manganese accumulation in the leaves. Less accumulation of calcium and potassium levels was observed in treatments fertilized only with nitrogen.
Produção de biomassa e de óleo essencial de Lippia origanoides (Verbenaceae) em função de doses de adubação química e orgânica
Keywords: cattle manure; Medicinal plants; mineral nutrition